Cloak of compassion, or evidence of elitism? An empirical analysis of white coat ceremonies. Issue 1 (21st December 2012) - Karnieli‐Miller, Orit; Frankel, Richard M; Inui, Thomas S
<x xml:space="preserve">Abstract</x> Context White coat ceremonies (WCCs) are widely prevalent as a celebration of matriculation in medical schools. Critics have questioned whether these ceremonies can successfully combine the themes of professionalism and humanism, as well as whether the white coat is an appropriate symbol. Objectives This study aimed to add a process of empirical assessment to the discussion of these criticisms by analysing the content and messages communicated during these ceremonies. Methods Multiple qualitative methods were used to discern the core meanings expressed in a sample of 18 ceremonies through the analysis of artefacts, words, phrases, statements and narratives. Out of a stratified random sample of 25 US schools of medicine conducting WCCs in 2009, 18 schools submitted video, audio and written materials. Results All ceremonies followed the same general format, but varied in their content, messages and context. Ceremonies included five principal descriptions of what is symbolised by the white coat, including: commitment to humanistic professional care; a reminder of obligations and privileges; power; the student's need to 'grow', and the white coat as a mantle. Statements about obligations were made three times more frequently than statements about privileges. Key words or phrases in WCCs mapped to four domains: professionalism; morality; humanism, and spirituality. Spoken narratives focused on humility and generosity. Conclusions The WCCs studied did not celebrate the status of an elite class, but marked the beginning of educational, personal and professional formation processes and urged matriculants to develop into doctors 'worthy of trust'. The ceremonies centred on the persons entering the vocation, who were invited to affirm its calling and obligations by donning a symbolic garb, and to join an ancient and modern tradition of healing and immersion in their community. The schools' articulated construct of the white coat situated it as a symbol of humanism. This study's findings may clarify and guide schools' choices in designing their own WCCs.